Translation in Historiography: The Garibay/León-Portilla Complex and the Making of a Pre-Hispanic Past - Payàs, Gertrudis (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractHistorians and anthropologists sometimes need to translate or to use translations in order to have access to sources written in other languages. Mexican historiography is one such case. Indeed, a good part of what we know about pre-Hispanic times has been revealed through translations. How the two most prominent Mexican Mesoamericanists have approached translation will be the focus of this work.